LIVING IN A BOARDING HOUSE: A PRIVACY MECHANISM IN ARCHITECTURE STUDENT’S PRIVATE STUDY ROOM - Setijanti, Purwanita; Cahyadini, Sarah; Narida, Tisya Surya (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2023)
Boarding houses, as a type of substitute residence, function not only to ensure the continuity of daily domestic activities, but also as a comfortable learning place for students as residents. The Multimodal learning methods, which is used in architectural studio learning, through design simulations making study mock-ups, requires the use of more than one strategy in the learning process. Because it requires a different concentration compared to unimodal students, learning privacy is not only needed for individual learning process, but also needed for group learning study activities. This research explores the privacy mechanism that occurs in boarding rooms as private workspaces for architecture students. Phenomenological qualitative methods are used, with data collection techniques through observation, interviews, and documents readings. The results of the study show that architecture students tend to organize to optimize space by modifying the spatial attributes. This is executed to provide the widest possible space for learning privacy, so that it’s multimodal learning activities could run as optimally as possible.